Serum 25-hydroxyvitamin D levels in relation to lipids and clinical outcomes in pregnant women with gestational diabetes mellitus: an observational cohort study - Chen, Wenqing (BMJ Open, 2020)
OBJECTIVE: The aim of the present study was to investigate whether 25-hydroxyvitamin D (25(OH)D) status at 24–28 weeks is associated with blood lipids and pregnancy outcomes in patients with gestational diabetes mellitus (GDM). DESIGN: We performed an observational cohort study. SETTING: The study was conducted in China. PARTICIPANTS: A total of 261 pregnant women diagnosed with GDM at 24–28 weeks of gestation in our hospital were included between June 2015 and December 2017. According to the levels of 25(OH)D, the women were divided into the G1 (<20 ng/mL) and G2 (≥20 ng/mL) groups. The levels of total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), TG/HDL-c and TC/HDL-c ratios were obtained from medical records. Pregnancy outcomes included gestational weeks of birth and delivery mode. Newborn information included birth weight and body length. Differences between groups were tested with adjusted multiple linear regression. RESULTS: The serum levels of 25(OH)D (14.1±3.4 ng/mL vs 28.5±6.5 ng/mL, p<0.001), TC (5.3±0.9 vs 5.6±0.8, p=0.006), HDL-c (1.8±0.4 vs 1.9±0.4, p=0.046) and LDL-c (2.5±0.6 vs 2.7±0.7, p=0.015) in the G2 group were significantly higher than those in G1 group, while TG/HDL-c ratios (1.43±0.7 vs 1.26±0.7, p=0.035) were significantly higher in the G1 group. Moreover, we failed to find a significant difference in pregnancy outcomes of mothers and newborns among the two groups (p>0.05). In models adjusting for maternal age, parity, height, blood pressure, socioeconomic status, educational attainment, pre-pregnancy body mass index, season and gestational age, maternal 25(OH)D was associated with TG/HDL-c ratios (B=−0.016; 95% CI= −0.025 to –0.006). CONCLUSION: We found that there was no relationship between vitamin D and pregnancy/neonatal outcomes in our study. Maternal 25(OH)D at 24–28 weeks was inversely associated with TG/HDL-c ratios.